Morel-Lavallée Lesion: Report of a Case of Unknown Mechanism. (17th February 2015) - Kontis, Elissaios; Vezakis, Antonios; Psychogiou, Vasiliki; Kalogeropoulos, Panagiotis; Polydorou, Andreas; Fragulidis, Georgios
Abstract : Morel-Lavallée lesions are cystic lesions occurring between the subcutaneous tissue and the underlying layer of a fascia. The most frequent mechanism of occurrence is posttraumatic, usually after degloving injuries. The chain of events leading to the occurrence of this lesion is the formation of a potential space between the subcutaneous tissue and the firmly attached deep fascia, which in turn fills with blood and/or lymph and/or necrotic fat, secondary to disruption of the capillaries. We present a case of a 74-year-old male patient with a cystic lesion of the lateral surface of his left thigh increasing in size over a period of six months. Despite the meticulous history acquisition, we were unable to reveal any alleged mechanism of injury of the area. The patient underwent an MRI which revealed an ovoid cyst. The patient underwent surgical excision of the cyst. The pathology examination revealed a simple cyst, lined by a fibrous capsule and filled with serosanguineous fluid, thus confirming the diagnosis. The patient made a full recovery and since has been asymptomatic.